Análise computacional dos campos de velocidade e temperatura do ambiente interno da usina termelétrica Santana - Amapá - OLIVEIRA FILHO, Álvaro Henriques de (Universidade Federal do Pará, 2014)
The numerical simulation of the airflow in internal environments is in the present time the most appropriate method for analysis of thermal comfort indoors. The airflow in these environments is configured as a complex one, therefore, in general, it is a combination of free-shear flow (jet) and of wall-shear flow, moreover, these are governed by inertia and buoyancy forces, characterizing a situation of mixing convection. The combination of these mechanisms creates an airflow with complex characteristics, as recirculation zones, vortices, detachment and re-attachment of boundary layer amongst others. Therefore, the precision of the solution will be directly connected, mainly, with the ability of the adopted turbulence model to reproduce the turbulent characteristics of the airflow and thermal transfers. The main objective of the present work was the computational simulation of the internal thermal environment of the enclosure which shelters the generators and the Wärtzilä engines of the thermo-electric power plant of Santana in the state of Amapá (Brazil). The mathematical formulation based on the solution of the general equations of conservation includes an analysis of the principal models of turbulence applied to the airflow inside the enclosure, as well as the heat transfer processes associated. The finite-volume numerical method is used in the discretization of the conservation equations, through the Fluent-Airpak software, for the analysis of the distribution of air velocity and temperature fields. The correct use of the software was tested and validated by successfully simulating problems solved by other authors. The numerical results of the airflow in the enclosure were compared with the experimental data and presented a good agreement, by considering the complexity of the simulated problem and the limitations and difficulties found during measurements. Moreover, simulations are presented of strategies for improvement of the thermal environment, based on the actual reality and on the results of the numerical simulations. Finally, simulations of a prototype solution are presented with the reduction of the internal temperature in the enclosure. This solution allows an increase of the exposure time inside the enclosure, from 20 up to 30%, and improves the thermal comfort of the thermo-electric power plant.